1998
DOI: 10.1002/(sici)1098-240x(199806)21:3<261::aid-nur9>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Finding a balance point: A process central to understanding family caregiving in Taiwanese families

Abstract: The grounded theory method was used to explore the psychosocial process of family caregiving to frail elders in Taiwan. Interview and observation data from 15 family caregivers were analyzed using constant comparative analysis. Caregivers used the process of finding a balance point to achieve or preserve equilibrium between and within caregiving and family life. Caregivers who did better in finding a balance point provided better quality care to frail elders. Caregivers who were good at finding a balance point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 0 publications
0
47
0
Order By: Relevance
“…One explanation for the similarity of findings may be that many of the Taiwanese families who participated in this study were middle-class and well-educated as compared to participants in previous Taiwanese studies. They may already have adopted Western values and beliefs (Shyu, Archbold, & Imle, 1998). As a result, the findings may not reflect how the adaptation occurs and is perceived in more traditional Taiwanese families.…”
Section: Discussionmentioning
confidence: 89%
“…One explanation for the similarity of findings may be that many of the Taiwanese families who participated in this study were middle-class and well-educated as compared to participants in previous Taiwanese studies. They may already have adopted Western values and beliefs (Shyu, Archbold, & Imle, 1998). As a result, the findings may not reflect how the adaptation occurs and is perceived in more traditional Taiwanese families.…”
Section: Discussionmentioning
confidence: 89%
“…This need for effort was underpinned by frequent descriptions of balancing as a dynamic process which was "fluid" (Shyu, Archbold, & Imle, 1998), "shifting" (Clare, 2002 "ongoing" (Brodsky, 1999) and "circular" (Pearce, Clare, & Pistrang, 2002). Shyu et al (1998), for example, described the balancing act of those caring for frail elderly relatives as being "like adjusting the shouldering point of a carrying pole according to the weight of the loads while walking." Moreover, as discussed above, even where reached, people saw the state of balance as fragile and in need of constant maintenance.…”
mentioning
confidence: 99%
“…This study also highlighted how DPNs made detailed readjustments to homecare arrangements prior to discharge, taking into consideration family lifestyles. Shyu et al (1998) reported that most family caregivers of frail, older people often fail to find a balance between caregiver and other roles. The DPNs' detailed readjustments may be vital for a successful discharge planning process and prevent the client/ family from returning to the hospital prematurely.…”
Section: Discussionmentioning
confidence: 99%